Museum education anthology, 1973-1983
1 online resource (260 pages)
Keywords: "Classic set of 45 articles from the first decade of the Journal of Museum Education and its predecessor, Roundtable Reports. Articles and essays focus on teaching strategies, introspective glances at the museum education field, reports of program successes and near successes, evaluative studies, and reviews of exhibitions and literature related to object-based learning. This title is sponsored by The Museum Education Roundtable. The Museum Education Roundtable (MER) is a non-profit organization based in Washington, DC, dedicated to enriching and promoting the field of Museum Education."--Provided by publisher.